Women in the Silent Cinema Histories of Fame and Fate - Förster, Annette (Framing Film, 2017)
This magisterial book offers comprehensive accounts of the professional itineraries of three women in the silent film in the Netherlands, France and North America. Annette Förster presents a careful assessment of the long career of Dutch stage and film actress Adriënne Solser; an exploration of the stage and screen careers of French actress and filmmaker Musidora and Canadian-born actress and filmmaker Nell Shipman; an analysis of the interaction between the popular stage and the silent cinema from the perspective of women at work in both realms; fresh insights into Dutch stage and screen comedy, the French revue and the American Northwest drama of the 1910s; and much more, all grounded in a wealth of archival research.